ECOLOGICAL NICHE THEORY (Nichespace, Niche Breadth and Niche Overlap, Competitive Superiority) Local Media in Central Java (Suara Merdeka And Tribun Jateng) - Monicaningsih, Aisyah (Interaksi: Jurnal Ilmu Komunikasi, 2017)
ABSTRACTThe Central Java Province has a wide range of local media both print and electronic media. The print media in Central Java is growing rapidly, as are present in the data follows the various print media market in Central Java. Suara Merdeka is one of the well-known mass media in Central Java Province, and is a daily morning newspaper published in the city of Semarang, Central Java. This daily has a circulation limited to the area of Central Java. The other one Tribun Jateng newspaper is a network Tribunnews newspaper, Kompas Gramedia Group. With the tagline "Spirit Baru Jawa Tengah", this newspapers targeting readers in Central Java have low price that only one hundred rupias so that all people can read a lot of information easily in physical form.As part of the print media, also affected the circulation of newspapers in Central Java, this research will discuss about how local media incase Suara Merdeka and Tribun Jateng consume resources the same and run a similar function in an environment in which the print media regional / local in which there is competition and live alongside each other. This study use qualitative research method, descriptive by interviewing informants from each newspaper, and study documents in the analysis using Niche Theory. This study aims to determine the Nichespace, Niche Breadth and Niche Overlap, Competitive Superiority of the local media that have popular areas in Central Java.The conclusion of this study is Nichespace terms both of the print media grab each local market both in terms of Central Java Region of the marketing and newspaper readers. Niche Breadth and Niche Overlap is different then the unit can coexist this is due to similarities between the two stories a bit, but both newspapers also must be careful to keep their respective markets both readers and ad target it to anticipate the competition fierce between the two mediums. Competitive Superiority media that most have the power to meet the needs of media audiences in Central Java primarily in Semarang is Suara Merdeka, but Suara Merdeka need to be vigilant if at any time the Tribune Jateng as a new medium that has the advantage of cheaper prices, easily obtained as in retailers who are in the traffic light in the city of Semarang can replace or destroy senior media like Suara Merdeka.Keywords: Media Local / Regional, Niche Theory, Space Niche, Niche Breadth and Niche Overlap, Competitive Superiority